(untitled) (International Journal of Engineering and Computer Science, 2013)
An effective and secure protection of sensitive information is the primary concerned in Communication systems or network storage systems. Never the less, it is also important for any information process to ensure data is not being tampered with. Encryption methods are one of the popular approaches to ensure the integrity and confidentiality of the protected information. However one of the critical vulnerabilities of encryption techniques is protecting the information from being exposed. To address these reliability problems, especially for large information content items such as secret images (satellite photos or medical images), an image secret sharing schemes (SSS) is a good alternative to remedy these types of vulnerabilities. With the rapid advancement of network technology, multimedia information is transmitted over the Internet conveniently. While using secret images, security issues should be taken into consideration because hackers may utilize weak link over communication network to steal information that they want. To deal with the security problems of secret images, various image secret sharing schemes have been developed. Because of the popular usage of images in network application in recent years, the way of sharing secret image has attracted wide attention. Noor and Shamir proposed first the idea of visual cryptography in 1994. The scheme provides an easy and fast decryption process that consists of Xeroxing the shares onto transparencies and then stacking them to reveal the shared image for visual inspection. The scheme which differs from traditional secret sharing does not need complicated cryptographic mechanisms and computations. Instead it can be done directly by the human visual system, without the aid of computers. However the generated noisy share may be suspicious to invaders and their scheme had 2n pixel expansion at best case. Visual cryptography scheme eliminates complex computation problem in decryption process, and the secret images can be restored by stacking operation. This property makes visual cryptography especially useful for the low computation load requirement. Iwamoto and Yamamoto in 2002, worked on an n-out-of-n visual secret sharing scheme for gray-scale images. They developed a secret sharing scheme that encodes grayscale images with a limited number of gray levels. The loss in the contrast is so large such that the recovered image is distorted. In other methods that construct a visual secret sharing scheme with a general access structure for plural secret images have been proposed .They have shown that most previous work of visual cryptography scheme for plural image suffered from the leak out of some information in each share about the other secret images of the scheme. The systems suffered from the deterioration of the image quality in addition to the weakness in the security and there are pixels R Yadagiri Rao International Journal Of Engineering And Computer Science 2:1 Jan 2013 (265-303) Page266 expansion step in all of method so needed some computation must be applied to reproduce the secret image. Taking limited bandwidth and storage into consideration two criteria pixel expansion and number of shares encoded is of significance. Smaller pixel expansion results in smaller size of the share. Encoding multiple secret images into the same share images requires less overhead while sharing multiple secrets. Meaningful shares avoid attention of hacker considering the security issues over the communication channels. To meet the demand of today’s multimedia.